1929 Iowa Acts 90, Carrying Firearms in Motor Vehicles, § 30 - (:unkn) unknown (General Publisher, 1929)
Prohibited carry of a gun or any firearms in or on a motor vehicle.
--
Keywords: TRANSFER & POSSESSION